Advances in microbial based bio-inoculum for amelioration of soil health and sustainable crop production - Aurodeepa Samantaray; Sourav Chattaraj; Debasis Mitra; Arindam Ganguly; Rahul Kumar; Ashish Gaur; Pradeep K.Das Mohapatra; Sergio de los Santos-Villalobos; Anju Rani; Hrudayanath Thatoi (Current Research in Microbial Sciences)
The adoption of sustainable agricultural practices is increasingly imperative in addressing global food security and environmental concerns, with microbial based bio-inoculums emerging as a promising approach for nurturing soil health and fostering sustainable crop production.This review article explores the potential of microbial based bio-inoculumsor biofertilizers as a transformative approach toenhance plant disease resistance and growth. It explores the commercial prospects of biofertilizers, highlighting their role in addressing environmental concerns associated with conventional fertilizers while meeting the growing demand for eco-friendly agricultural practices. Additionally, this review discusses the future prospects of biofertilizers, emphasizing the ongoing advancements in biotechnology and formulation techniques that are expected to enhance their efficacy and applicability. Furthermore, this article provides insights into strategies for the successful acceptance of biofertilizers among farmers, including the importance of quality control, assurance, and education initiatives to raise awareness about their benefits and overcome barriers to adoption. By synthesizing the current research findings and industrial developments, this review offers valuable guidance for stakeholders seeking to exploit the potential of biofertilizers or beneficial microbes to promote soil health, ensure sustainable crop production, and addressing the challenges of modern agriculture.